The causal effect of glaucoma and diabetic retinopathy: a Mendelian randomization study - Shuyun Chen; Ming Lin; Yu Hong (Diabetology & Metabolic Syndrome)
Abstract Background Previous research showed that there is an important association between glaucoma and diabetic retinopathy (DR). However, the relationship has not been clarified. In this study, we attempted to evaluate it. Methods We conducted bidirectional Two-sample Mendelian randomization (MR), Multivariable Mendelian randomization (MVMR), and Mediation analysis. The Inverse-variance-weighted method was adopted as the main MR method, supplemented by MR-Egger, weighted median, weighted mode, and simple mode. Results The results of forward MR analysis suggested that glaucoma [p = 0.001, odds ratio (OR) = 1.080] and intraocular pressure (IOP) (p = 0.019, OR = 1.100) as risk factors for DR. The reverse MR found that DR was a risk factor for glaucoma (p = 0.039, OR = 1.024) and IOP (p = 0.010, OR = 1.057). The results of MVMR analysis demonstrated that glaucoma (p = 0.046, OR = 1.069) remained an independent risk factor for DR. The bidirectional relationship between glaucoma and DR is mediated by IOP, according to the results of the Two-step MR analysis. Besides, glaucoma contributed to the positive causal link that exists between IOP and DR. Conclusion The findings demonstrated a reciprocal causal link between glaucoma and DR, with a possible mediating function for IOP. Moreover, glaucoma played an important mediator of IOP as a risk factor for DR. It offers recommendations for the early prevention of both DR and glaucoma.